16.5k views
5 votes
What are the solutions of the equation (2x + 3)2 + 8(2x + 3) + 11 = 0? Use u substitution and the quadratic formula to solve

X-

User Theforce
by
5.8k points

2 Answers

6 votes

Answer:

B Edge 2022

Explanation:

User JacopKane
by
6.1k points
4 votes

Answer:


x=(-7+√(15))/(2)


x=(-7-√(15))/(2)

Step-by-step explanation:

we have


(2x+3)^2+8(2x+3)+1=0

Let


u=(2x+3)

substitute the variable

so


u^2+8u+1=0

we know that

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0

is equal to


x=\frac{-b(+/-)\sqrt{b^(2)-4ac}} {2a}

in this problem we have


u^2+8u+1=0

so


a=1\\b=8\\c=1

substitute in the formula


u=\frac{-8(+/-)\sqrt{8^(2)-4(1)(1)}} {2(1)}


u=\frac{-8(+/-)√(60)} {2}


u=\frac{-8(+/-)2√(15)} {2}


u=-4(+/-)√(15)

so


u_1=-4+√(15)


u_2=-4-√(15)

Find the value of x

Remember that


u=(2x+3)

First solution


-4+√(15)=(2x+3)


2x=-4+√(15)-3


2x=-7+√(15)


x=(-7+√(15))/(2)

Second solution


-4-√(15)=(2x+3)


2x=-4-√(15)-3


2x=-7-√(15)


x=(-7-√(15))/(2)

User Zaur Nasibov
by
6.1k points